Reduced naïve CD8+ T‐cell priming efficacy in elderly adults. Issue 1 (15th October 2015) - Briceño, Olivia; Lissina, Anna; Wanke, Kerstin; Afonso, Georgia; von Braun, Amrei; Ragon, Kristanto; Miquel, Tiphaine; Gostick, Emma; Papagno, Laura; Stiasny, Karin; Price, David A.; Mallone, Roberto; et al.
Summary: Aging is associated with impaired vaccine efficacy and increased susceptibility to infectious and malignant diseases. CD8 + T‐cells are key players in the immune response against pathogens and tumors. In aged mice, the dwindling naïve CD8 + T‐cell compartment is thought to compromise the induction of de novo immune responses, but no experimental evidence is yet available in humans. Here, we used an original in vitro assay based on an accelerated dendritic cell coculture system in unfractioned peripheral blood mononuclear cells to examine CD8 + T‐cell priming efficacy in human volunteers. Using this approach, we report that old individuals consistently mount quantitatively and qualitatively impaired de novo CD8 + T‐cell responses specific for a model antigen. Reduced CD8 + T‐cell priming capacity in vitro was further associated with poor primary immune responsiveness in vivo . This immune deficit likely arises as a consequence of intrinsic cellular defects and a reduction in the size of the naïve CD8 + T‐cell pool. Collectively, these findings provide new insights into the cellular immune insufficiencies that accompany human aging.